2019
DOI: 10.3389/fonc.2019.00150
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TF-AKT/ERK-EGFR Pathway Suppresses the Growth of Hepatocellular Carcinoma

Abstract: Tissue factor (TF) is a transmembrane glycoprotein to initiate blood coagulation and frequently overexpressed in a variety of tumors. Our previous study has showed that the expression of TF is upregulated and correlated with prognosis in hepatocellular carcinoma (HCC). However, the role and molecular mechanism of TF in the growth of HCC are still unclear. In vitro and in vivo functional experiments were performed to determine the effect of TF on the growth of HCC cells. A panel of biochemical assays was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The activation of EGFR in cancer cells is known to induce the activation of extracellular-regulated kinase (ERK) or Akt (protein kinase B; PKB) signaling pathways ( 67 , 68 ). Thus, we investigated the mRNA expression levels of ERK1/2 (also known as MAPK3/1) and AKT1 in porcine COCs after IVM.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of EGFR in cancer cells is known to induce the activation of extracellular-regulated kinase (ERK) or Akt (protein kinase B; PKB) signaling pathways ( 67 , 68 ). Thus, we investigated the mRNA expression levels of ERK1/2 (also known as MAPK3/1) and AKT1 in porcine COCs after IVM.…”
Section: Discussionmentioning
confidence: 99%
“…Given that disorder lipid metabolism is closely associated with non-alcoholic fatty liver disease (NAFLD) and has been growingly considered a hallmark of cancer cells (Cingolani and Czaja, 2016;Tian et al, 2019), It is reasonable that MDGs exerted great impact on non-viral HCC through regulation of lipid metabolism and homeostasis. In addition, KEGG analysis suggested that EGFR and P53 pathways were also significantly enriched, which were involved in the pathogenesis and tumorigenesis of HCC (Xie et al, 2018;Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the viral supernatant was, respectively, collected 24, 48, 72, 96 h following transfection, filtered through a 0.20 μm filter, and concentrated. Using the polybrene (Solarbio, H8761), A2780, OVCAR-3 cells were transfected with pCDH-Neo-Venus-survivin or pCDH-Neo-Venus/DEST, followed by incubation with 48 h for the subsequent trials (17, 18).…”
Section: Methodsmentioning
confidence: 99%